Sex and consent in contemporary youth sexual culture: the 'ideals' and the 'realities'. Issue 3 (4th May 2021) - Setty, Emily
ABSTRACT: Sexual consent has increasingly become a central component of Relationships and Sex Education. This paper draws upon findings from qualitative research conducted with teenagers in England, which explored their perspectives on consent within their contemporary youth sexual cultures, including in digital (sexting) contexts. The findings suggest that young people's definitions of consent often did not correspond to the socially- and contextually contingent realities of negotiating and establishing consensual sex(ting). While young people's contemporary sexual cultures may look somewhat different, longstanding gender norms and sexual scripts shaped their attitudes towards consent. The implications of the findings for RSE are discussed, including the need for more collaborative dialogue and exchange between educators and learners that engages with the situated realities of contemporary youth sexual culture.